Innovaciones y desafíos del Plan Abre: Institucionalidad, capacidades estatales y sostenibilidad (Papeles, 2021)
This article studies the experience of Abre Plan for integral improvement of neighbourhoods, implemented by Santa Fe Province Government (Argentina) during 2013-2019 period, as a relevant case study in the field of urban social policies, which allows for identifying innovations, lessons and challenges of this field of study. First, it analyzes the problem that gives rise to the Plan, its strategy and the characteristics assumed by its institutionalization process. Second, the article investigates the state capabilities of the Plan, especially considering how the integrality proposed in the formulation becomes operational in the territory. For this purpose, it examines the territorial capability to simultaneously address urban and social problems; a set of integrating tools that include planning, coordination, monitoring and evaluation and the role of territorial teams as promoters of integrality in territory. Third, it analyzes the special features of Abre Plan in Rosario city, highlighting the key attributes of the municipal state capability which facilitated its implementation. Finally, it reflects upon the main challenges of the Plan, recognizing that its sustainability is still an open question.
Keywords: institutionality; state capabilities; Abre Plan; integrality; territory